The Use of Short Story To Increase Vocabulary of The Eighth Grade Students of SMP Negeri 2 Poso Pesisir Utara - Niluh Michelle Natania; Darmawan, Darmawan; Zarkiani Hasyim (CV. Ulil Albab Corp, 2025)
The objective of this research is to investigate whether the use of short stories can increase the vocabulary of eighth-grade students at SMP Negeri 2 Poso Pesisir Utara. The researcher employed a quasi-experimental design, involving two classes: an experimental group and a control group. A total sampling technique was used to select 47 students as the sample for this study. The data were analyzed using a t-test. Based on the data analysis, the mean score of the experimental group's pre-test was 33.74, while the control group's mean score was 37.15. After the treatment, the experimental group's post-test mean score increased to 80.59, which was higher than the control group's post-test mean score of 49. The t-test comparison revealed that the t-counted value (6.45) was greater than the t-table value (1.684), indicating a significant difference. Therefore, H1 is accepted and H0 is rejected. It can be concluded that the application of short stories has a significant effect on increasing the vocabulary of eighth grade students at SMP Negeri 2 Poso Pesisir Utara.